Evaluation Of Railway Maintenance at Light Rail Transit Jakarta: Perawatan Jalan Rel di Light Rail Transit Jakarta - arifin, kurniawan; Wibowo, Heriyanto (Fakultas Teknik Transportasi dan Logistik Trisakti, 2024)
The capital city of DKI Jakarta is a densely populated area and the main factor for traffic jams. The DKI Jakarta Provincial Government is developing Light Rail Transit (LRT)-based transportation to reduce congestion at certain points. Railways are a construction unit made of steel, concrete or other constructions that are located on the surface that directs the railroad. Economically, the construction and maintenance of road construction rails can be carried out efficiently and still guarantee safety and comfort. The rail system is divided into upper and lower structures, the superstructure must include: geometry, free space, axle load and frequency, the geometric requirements that must be met are: Curve, Gauge, Cannot. In order to support the safe operation of the train, it is necessary to maintain bends every 3 months (preventive) so that the condition of the railroad tracks when the train passes does not falter or fall. Improvement of the rail geometry at bends is carried out by measuring the 3 point versine method which aims to restore the condition of the rail according to the conditions or design, calculated through the transition curve, full curve, until the end of the curve.